Synthesis, Biological Evaluation, and SAR Studies of 14β-phenylacetyl Substituted 17-cyclopropylmethyl-7, 8-dihydronoroxymorphinones Derivatives: Ligands With Mixed NOP and Opioid Receptor Profile - Kumar, Vinod; Polgar, Willma E.; Cami-Kobeci, Gerta; Thomas, Mark P.; Khroyan, Taline V.; Toll, Lawrence; Husbands, Stephen M. (Frontiers in Psychiatry, 2018)
A series of 14beta-acyl substituted 17-cyclopropylmethyl-7,8-dihydronoroxymorphinones compounds has been synthesized and evaluated for their affinity and efficacy for mu (MOP), kappa (KOP) and delta (DOP) opioid receptors and nociceptin/orphanin FQ peptide (NOP) receptors. The majority of the new ligands displayed good binding affinities for all four receptors, with affinities for NOP of particular interest as most classical opioid ligands do not bind to NOP receptors. The predominant activity in the [35S]GTPgammaS assay was partial agonism at each receptor. The results are consistent with our prediction that an appropriate 14beta side chain would access a binding site within the NOP receptor and result in substantially higher affinity than displayed by the parent compound naltrexone. Molecular modelling studies, utilizing the recently reported structure of the NOP receptor, are also consistent with this interpretation.